FACTORS IMPEDING THE ROLE OF INTERMEDIARIES IN URBAN FISH AND FISHERIES SUPPLY CHAIN; A CASE OF DAR ES SALAAM, TANZANIA - Ibrahim M. Issa; Mzomwe Mazana; Kirumirah Mubarack; Emmanuel J. Munishi (Universitas PGRI Madiun, 2022)
Despite the critical role played by intermediaries in supply chain and trade, along with various initiatives undertaken to enhance this role, fish and fisheries traders in Dar es Salaam-Tanzania are still discontented with the intermediaries’ inability to undertake supply chain roles. This paper examined the impediments to intermediaries’ role in urban fish and fisheries supply chain and recommended strategies for improving the same. Qualitative approach was adopted and data were drawn from a purposive sample of 73 respondents through in-depth interviews, focus group discussions and non-participant observation. Accordingly, intermediaries’ role in urban fish and fisheries supply was impeded by poor transportation, inadequate storage facilities, and inability to improve quality and poor marketing services. The study recommends some ways to alleviate the impediments. These include ensuring suitable advocacy, regulations and knowledge, road infrastructures; provision of insurance covers during transportation; installation of modern storage, handling and packaging facilities and ensuring adequate power supply. The inability to value addition should be alleviated through sensitization of intermediaries on value addition, intermediaries should be empowered financially to buy adequate handling and storage facilities; government establish modern fishing processing industries as well as enforcement of quality assurance and standards for fish products. To improve marketing services, fishermen and intermediaries should be devised with innovative ways of determine appropriate market prices, fishermen and intermediaries be sensitized on urban markets as well as ensuring effective and smooth exchange of marketing information among stakeholders. Therefore, impediments to Intermediaries’ role in Urban fish and fisheries supply chain in Dar es Salaam can be overcome through improvement in transportation, storage, value addition and quality improvement as well as improving marketing services.